City centre management: Dutch and British experience of a new form of planning - ENNEN, Elke; ASHWORTH, Gregory (European Spatial Research and Policy, 1998)
The contemporary city centre is overloaded with activities and with expectations. New forms of managing city centres which have been labelled 'city centre management' try to deal with this new situation. This article compares the experiences of two Western European countries, each with a relatively long tradition of public planning intervention, namely the Netherlands and the United Kingdom.